Multichromatic fluorescence towards aberrant proteinaceous aggregates utilizing benzimidazole-based ICT fluorophores - An, Jusung; Jangili, Paramesh; Lim, Sungsu; Kim, Yun Kyung; Verwilst, Peter; Kim, Jong Seung (Kluwer Academic Publishers, 2021)
The pathological origin of Alzheimer’s disease (AD) remains uncharted terrain, despite intensive investigation. Discriminating aberrant proteinaceous deposits, such as β-amyloid (Aβ) and (hyperphosphorylated) tau protein by imaging methods, is a vital tool to support investigations towards the network of interacting features that results in AD pathology. In this context, multispectral fluorescence imaging (MSFI) has drawn much attention enabling the distinction of several analytes with merely a single fluorophore emitting a multichromatic fluorescent signal. Herein, we developed three kinds of benzimidazole-derived fluorescent dyes, BZ1–BZ3. The photophysical properties and intramolecular charge transfer (ICT) characteristics of the probes were evaluated in various solvents. Furthermore, a benzimidazole-associated polar-sensitivity displayed multichromatic behavior and enabled the visualization of minute differences in microenvironmental polarity between Aβ and tau aggregates, resulting in different maximal fluorescent emission wavelengths. Indeed, BZ2 demonstrated an approximately 30 nm bathochromic shift in maximal fluorescent emission. All these observations offer a potential for the development of a future generation of benzimidazole-derived ICT-based fluorescent probes.